Influence of Design Elements of Mobile Push Notifications on Mobile App User Interactions - Wohllebe, Atilla; Adler, Manuel Rolf; Podruzsik, Szilárd (International Journal of Interactive Mobile Technologies (iJIM), 2021)
With the increasing relevance of mobile apps for companies, push notifications to address app users are also becoming more important. While the acceptance factors of push notifications have already been extensively researched, the effect of the different design elements on user interaction by opening the mobile app is still completely unexplored. Based on existing scientific findings from related fields, especially banner advertising and e-mail marketing, the authors first develop hypotheses on the effect of title, button and image on user interaction with push notifications. In several experiments the hypotheses are tested using the example of a mobile shopping app. The results are evaluated using Chi-square test and Cramer’s V. While the use of a title seems to have a positive effect on interaction rates, the hypotheses on the positive effect of buttons and images on interaction rates have to be rejected.